Answer:
-2
Step-by-step explanation:
Answer:
in my ipinion...
Step-by-step explanation:
let a no.be x
1/3*x+77=33
1/3*x=-44
x=-44*3
x=-132
a + b = 88 <span>
<span>
</span><span>ab = y
</span><span>
</span><span>a = 88 - b
</span><span>
</span><span>y = (88 - b)*b
</span>
<span>y = -b^2 + 88b
</span><span>
</span><span>Take the derivative and set equal to 0
</span><span>
</span><span>y' = -2b + 88 = 0
</span><span>
</span><span>2b = 88
</span>
<span>b = 44 </span></span>
<span><span>a=44</span></span>
<span><span> both numbers are 44</span></span>